Topic Modeling for Evolving Textual Data Using LDA, HDP, NMF, BERTOPIC, and DTM With a Focus on Research Papers - Pavithra; Savitha (Journal of Technology and Informatics (JoTI), 2024)
As the volume of academic literature continues to burgeon, the necessity for advanced tools to decipher evolving research trends becomes increasingly apparent. This study delves into the utilization of topic modeling techniques—specifically Latent Dirichlet Allocation (LDA), Hierarchical Dirichlet Process (HDP), Non-negative Matrix Factorization (NMF), BERTopic, and Dynamic Topic Modeling (DTM)—applied to a dynamic corpus of research papers. Our research endeavors to confront the challenges posed by capturing temporal dynamics, evolving terminology, and interdisciplinary themes within academic literature. Through a comprehensive comparative investigation of these models, we assess their efficacy in extracting and tracking research topics over time. While DTM exhibited the highest term topic probability, its inclusion of non-meaningful words proved to be a hindrance to its suitability. Conversely, NMF, HDP, LDA, and BERTopic demonstrated comparable performance in topic extraction. Surprisingly, DTM emerged as the most effective model in our research, showcasing its prowess in navigating the intricacies of evolving research trends.